Seed Dormancy and Germination Responses of Salicornia brachiata: Towards Sustainable Cultivation and Conservation in Saline Habitats - Sandani M. Gunasekara; Chamara L. Mendis; Dinum Perera; Malaka M. Wijayasinghe (Plants)
Salicornia brachiata Roxb., an economically and ecologically significant halophytic species native to Sri Lanka, produces dimorphic seeds. Despite their importance for commercial cultivation and conservation, germination studies of these dimorphic seeds remain limited. This study investigated the effects of temperature (25 °C, 30 °C, 35 °C), gibberellic acid (GA3) treatment, geographic location of seed source (Jaffna vs. Puttalam coastal regions), seed type (central vs. lateral), and perianth presence/absence on germination under controlled conditions. Our results show that temperature, GA3, and geographic location of the seed source significantly influenced seed germination. This study presents the first documented evidence of physiological dormancy (PD) in S. brachiata seeds, with successful dormancy breaking achieved using GA3 treatment at 25 °C. Although perianth and seed type alone had no significant direct effects on germination, they were involved in multiple significant interactions—two-, three-, and four-way—with other factors. These findings highlight the multifactorial regulation of S. brachiata seed germination, suggesting that tailored propagation strategies, incorporating environmental and physiological variables, can optimize germination. These findings offer practical solutions for enhancing germination in saline agriculture and habitat restoration efforts of S. brachiata.